Female genitourinary tract melanoma: mutation analysis with clinicopathologic correlation. Issue 6 (December 2018) - Saglam, Ozlen; Naqvi, Syeda M.H.; Zhang, Yonghong; Mesa, Tania; Teer, Jamie K.; Yoder, Sean; Lee, Jae; Messina, Jane
Abstract : Female genitourinary tract melanoma (FGTM) is a rare and often-fatal form of mucosal melanoma. We describe our institutional experience with 55 cases of FGTM, 16 of which were evaluated with next-generation sequencing targeting 151 cancer-associated genes. Tumors tended to be thicker than conventional melanoma at presentation (median: 3.2 mm), were frequently ulcerated (50%), and characterized by incomplete initial resections. Regional lymph nodes showed tumor involvement at presentation in 28% of cases. With a median follow-up of 23.6 months, the median recurrence free survival was 14.5 months and the median overall survival was 29.6 months. Genomic analysis revealed mutually exclusive mutations in TP53 and KIT in 25%, while 19% of cases showed BRAF mutation. NRAS mutation was found in 13% of cases. Mutation in ATRX, previously undescribed in mucosal melanoma, was seen in three (10%) of 16 patients. Only invasive melanoma cases were included in statistical analyses. Patients with three or more mutations had marginally worse overall survival rates than those with two or less ( P =0.07). Further studies are required for potential adjuvant treatment modalities to improve survival outcomes of FGTM.